Sosialisai Penetapan Harga Jual Produk Terhadap Profit UMKM di Kelurahan Karang Joang - Jepri Jepri; Karina Amilia; Franky Purnama Wijaya (Abdimas Universal, 2024)
Almost all and the majority of MSME owners in Karang Joang Village, Balikpapan City, precisely in Gang Banyumas KM 15 RT 32 and its surroundings, have an inadequate understanding of the proper calculation of product selling prices. MSME owners have not identified and calculated costs optimally, causing the profit generated to be less than optimal. In response to this problem, the researcher will implement the work program "Socialization of Product Selling Price Determination towards MSME Profit in Kelurahan Karang Joang" to MSME owners and residents of RT 32 and its surroundings in KM 15 Karang Joang Village, North Balikpapan District, Balikpapan City. The purpose of this socialization is to increase the insight and knowledge of MSME owners in identifying costs and setting product selling prices more optimally. This socialization activity was attended by 33 participants, including MSME owners and local residents. The results of this activity showed an increase in understanding among the participants regarding the method of determining the right product selling price. MSME owners began to be able to identify the costs involved and calculate the selling price more accurately, so that the potential profit obtained is maximized.